Beating the urban heat: Situation, background, impacts and the way forward in China - He, Bao-Jie; Wang, Junsong; Zhu, Jin; Qi, Jinda (Renewable & sustainable energy reviews, 2022)
This paper reviews urban heat (UrHT) challenges following the SBAR (situation, background, assessment and recommendation) framework. The results indicate that heatwaves become more frequent, lasting and intense, especially after 1990s. Above 1960s level, heatwaves across China doubled in both magnitude and frequency by 2018. Jianghuai and Southern China underwent the largest magnitude and most widespread increases. Under 1.5 °C warming limit, the average heatwave days and duration across China will increase by 10.8 days and 3.9 days. Drought–heatwave co–occurrence is increasingly frequent at 7–11%/decade (from 1961 to 2018) and the co–occurrence leads to more intense heatwaves. UHIs are a common issue for almost all Chinese cities and UHIs have been aggravating annually. Daytime UHIs peak in summer, indicating the synergies with heatwaves. The synergies are prominent in southeastern cities for strong summer daytime UHIs in eastern cities and intense heatwaves in southern regions. UrHTs have not been recognised and there are no dedicated/mandatory plans. Mega–challenges of climate change, rapid urbanisation, carbon– and labour–intensive economic growth and demographic changes can potentially lock China into UrHT challenges. Addressing UrHT challenges is urgent in China not only for environmental, ecosystem, social and health consequences, but also for economic impacts relevant to labour, capital, and goods or services. Efforts are suggested in technical improvement, policy formulation, social participation, economic investment and co-benefit approach recognition. Overall, this paper provides a comprehensive understanding of heat–related challenges in China and can guide the creation of cool cities and communities in practice. [Display omitted] •Almost all cities in China are under the impacts of urban heat islands.•Heatwaves and urban heat islands can synergise, especially in Southeastern China.•China has not well recognised urban heat challenges and no dedicated plan.•UrHT affects economic productivity by affecting outputs, labour, capital and goods.•UrHT may drive population migrating out the extreme heat areas.